Legitimacy the right to rule in a wanton world - Applbaum, Arthur Isak, 1957- (Harvard University Press, 2019)
What makes a government legitimate? The dominant view is that our public officials have the right to rule us, even if they are unfit or unfair, as long as they gain power through procedures based on our consent. In Legitimacy, Arthur Applbaum argues that adherence to procedure is not enough, that legitimacy must also depend on the substance of laws, policies, and practices. Applbaum holds that a government cannot be legitimate unless it upholds three principles. These are: 1. liberty, necessary to protect against barbarism, 2. equality, to protect against despotism and to help the vulnerable, and 3. agency, according to which authorities treat citizens as competent, independent agents and, within limits, respect the mandate that citizens have given them. Today, Applbaum writes, the greatest risk to our democracies is the violation of the third principle, as wanton leaders threaten to act in an unconstrained, incoherent, and inconsistent manner that undermines respect for others as moral agents. Working out the extended implications of his principles, Applbaum shows that legitimacy also requires respect for counter-majoritarian institutions and practices such as judicial review, independent administrative agencies, and civil disobedience.--